Optimization of gravity-driven membrane (GDM) filtration process for seawater pretreatment. (15th April 2016) - Wu, Bing; Hochstrasser, Florian; Akhondi, Ebrahim; Ambauen, Noëmi; Tschirren, Lukas; Burkhardt, Michael; Fane, Anthony G.; Pronk, Wouter
Abstract: Seawater pretreatment by gravity-driven membrane (GDM) filtration at 40 mbar has been investigated. In this system, a beneficial biofilm develops on the membrane that helps to stabilize flux. The effects of membrane type, prefiltration and system configuration on stable flux, biofilm layer properties and dissolved carbon removal were studied. The results show that the use of flat sheet PVDF membranes with pore sizes of 0.22 and 0.45 μm in GDM filtration achieved higher stabilized permeate fluxes (7.3–8.4 L/m 2 h) than that of flat sheet PES 100 kD membranes and hollow fibre PVDF 0.1 μm membranes. Pore constriction and cake filtration were identified as major membrane fouling mechanisms, but their relative contributions varied with filtration time for the various membranes. Compared to raw seawater, prefiltering of seawater with meshes at sizes of 10, 100 and 1000 μm decreased the permeate flux, which was attributed to removal of beneficial eukaryotic populations. Optical coherence tomography (OCT) showed that the porosity of the biofouling layer was more significantly related with permeate flux development rather than its thickness and roughness. To increase the contact time between the biofilm and the dissolved organics, a hybrid biofilm-submerged GDM reactor was evaluated, which displayed significantly higher permeate fluxes than the submerged GDM reactor. Although integrating the biofilm reactor with the membrane system displayed better permeate quality than the GDM filtration cells, it could not effectively reduce dissolved organic substances in the seawater. This may be attributed to the decomposition/degradation of solid organic substances in the feed and carbon fixation by the biofilm. Further studies of the dynamic carbon balance are required. Graphical abstract: Highlights: The use of MF in GDM filtration achieved higher stabilized flux than that of UF. Pore constriction and cake filtration were major fouling mechanisms of GDM system. Prefiltering of seawater decreased flux due to removal of eukaryotes. More porous biofouling layer led to higher stabilized flux. Integration of biofilm reactor with submerged GDM reactor improved flux.